Primeiro módulo de cohomologia do complexo cotangente de curvas monomiais - Bruno Rodrigues dos Santos (2016)
The aim of this work is to present a rather explicit description of the first cohomology module of the cotangent complex of a monomial curve through the construction of the cotangent complex of a morphism introduced in a celebrated work of LichtenbaumSchlessinger, construction which generalizes the truncated cotangent complex introduced by A. Grothendieck.